Legal Analysis of Non-Halal Funds from P2P Investors in The Sharia Fintech Industry According to POJK Number 77 of 2016 - Yulya, Yulya; Hakim, Lukmanul (Universitas Muhammadiyah Surakarta, 2025)
This study is motivated by the strict provisions in Financial Services Authority Regulation (POJK) Number 77 of 2016 regarding the requirement for the halal status of investor funds on sharia fintech platforms. This condition creates a legal gap between positive law and sharia principles, which could threaten the integrity and public trust in the sharia financial industry. The main issue of this study is how to conduct a juridical analysis of non-halal funds from P2P investors in the Islamic fintech industry according to POJK Number 77 of 2016 and its implications for Islamic law. The methodology used is a normative (doctrinal) legal study with a legislative, conceptual, and Islamic fatwa approach. Data was collected through a literature survey on legislation, DSN-MUI fatwas, and Islamic economic law literature. Analysis was conducted to identify relationships and gaps using teleological, methodical, and grammatical interpretations between POJK 77/2016 and Islamic legal principles. The results of the study show that POJK 77 of 2016 does not explicitly regulate the halal status of investor funds in sharia fintech, thus potentially violating sharia principles, such as the prohibition of riba, gharar, and maysir. This disharmony causes legal uncertainty and can invalidate sharia financing agreements. This study recommends the establishment of specific regulations for sharia fintech that integrate DSN-MUI provisions, require verification of investor funds, and strengthen the role of the Sharia Supervisory Board (DPS). Thus, the Islamic fintech system in Indonesia can operate legally, ethically, and in accordance with the principles of Islamic maqashid.